Pendampingan dan Pengembangan Kurikulum Program Studi Sarjana Terapan (D4) Teknik Elektronika FT UNM - Hendra Jaya; Ummiati Rahmah; Aulia Sabril; Mustamin Mustamin; Dary Mochamad Rifqi (STIKes Ibnu Sina Ajibarang, 2023)
The targets and outputs produced in accordance with the activity plan are as follows: 1) The creation of lecturers of the Vocational Education Study Program (D4) Electronic Engineering FT UNM can increase knowledge of developing curriculum in the Vocational Education Study Program (D4) Electronic Engineering FT UNM; 2) The completion of curriculum documents in the Vocational Education Study Program (D4) Electronic Engineering FT UNM. The method used in this community service activity is to use lectures, questions and answers, exercises and through simulations. The lecture method is used to provide theoretical information about curriculum improvement. This training can help change the mindset of lecturers majoring in electronic engineering education, by increasing their knowledge about curriculum development so that they can formulate course study materials that are in accordance with the ELOs of the applied electronic engineering undergraduate study program. In addition, this is also expected to provide solutions for study programs that have difficulty meeting product needs in the form of RPS. The training provided at this time may not be optimal in empowering lecturers in curriculum development, so more follow-up activities are needed that are organized and carried out by the head of the study program.